Patterns of care and economic consequences of using bone-targeted agents for castration-sensitive prostate cancer patients with bone metastases to prevent skeletal-related events in Switzerland – the SAKK 95/16 prostate study - Sandro T. Stoffel; Roger von Moos; Beat Thürlimann; Richard Cathomas; Silke Gillessen; Ursina Zürrer-Härdi; Thomas von Briel; Sandro Anchisi; Anita Feller; Corinne Schär; Daniel Dietrich; Matthias Schwenkglenks; et al. (Swiss Medical Weekly, 2021)
BACKGROUND